Diseño y desarrollo de un sistema de gestión de calidad ISO 9001:2008 para una empresa metalmecánica - Hernández Cheing, María Elena (2009)
This study is designed to develop a Quality Management System for a metal mechanic industry. First, an internal audit allowed us to take a broader view of the state of the company against the guidelines to implement a Quality Management System. This audit determined that the company had a 25.8% compliance with the requirements of the Norm. The development of the System began with the establishment of the goals to be accomplished. Then, the company's existing processes were analyzed, aligned with the ISO 9001:2008 Norm, and assessed for criticality. By defining the critical processes, we established indicators to regularly evaluate continuous improvement. The basic documented procedures set by the ISO 9001:2008 Norm were developed. Lastly, there was a second internal audit to determine the percentage of improvement obtained the compliance rate increased to 74.19%. This percentage is not enough to certify the company, but it built a foundation for the company to reduce the number of nonconformities and plan a certification audit in a period of no more than a year.